Friction and bureaucratic control in authoritarian regimes. Issue 4 (5th April 2020) - Chan, Kwan Nok; Fan, Shiwei
Abstract: Democracies deliberately create "friction" in bureaucratic processes, using inefficiencies to mitigate the impact of government transitions and asymmetric information on leaders' ability to exert control. With far more centralized power, would authoritarians prefer less friction? We argue that they do not. In fact, excess friction is actively supplied to hinder bureaucratic coordination independent of or even in opposition to top‐down control, leaving the central leaders the only player powerful enough to organize complex actions. Our analysis of data on the Chinese government indicates that bureaucrats are systematically sent to unfamiliar work environment, and that agencies that are more exposed to the resultant inefficiencies are also more likely to come under direct control by senior Politburo members. The pattern of targeted intervention indicates that bureaucratic control in authoritarian regimes is predicated not only on centralized power in general but also the deliberate supply of friction to obstruct independent actions from the bottom up.